Determination of Selected Amino Acids in Serum of Patients with Liver Disease - Kanďár, Roman; Drábková, Petra; Toiflová, Tereza; Čegan, Alexander (Advances in clinical and experimental medicine, 2016)
BACKGROUND: The determination of amino acids can be a reliable approach for extended diagnosis of liver diseases. This is because liver disease can be a cause of impaired amino acid metabolism. Therefore, a method for the determination of serum amino acids, applicable for clinical purposes, is necessary. OBJECTIVES: The aim of this study was to find differences in the levels of selected amino acids between patients with liver disease and a control group. MATERIAL AND METHODS: Samples of peripheral venous blood were obtained from a group of patients with liver disease (n = 131, 59 women at an average age of 60 years and 72 men at an average age of 52 years) and a control group (n = 105, 47 women at an average age of 62 years and 58 men at an average age of 58 years). Before the separation, the amino acids were derivatized with naphthalene-2,3-dicarboxaldehyde. For the separation, reverse phase column was used. The effluent was monitored with a fluorescence detector. RESULTS: There were significant differences in the concentrations of some amino acids between the patients and the control group, but also between women and men. Correlations between some amino acids and markers of liver blood tests and lipid metabolism were observed. CONCLUSIONS: A simple, relatively rapid and selective HPLC method with fluorescence detection for the determination of selected amino acids in serum has been developed.
Keywords: aminokyseliny; Analysis of Variance; Male; Statistics, Nonparametric; neparametrická statistika; vysokoúčinná kapalinová chromatografie; Case-Control Studies; mužské pohlaví; kalibrace; Chromatography, High Pressure Liquid; Fluorescence; limita detekce; lidé; ženské pohlaví; studie případů a kontrol; analýza rozptylu; Humans; Limit of Detection; Liver Diseases; Female; Calibration; lidé středního věku; fluorescence; nemoci jater; Amino Acids; Middle Aged